2001
DOI: 10.1016/s0029-7844(01)01379-5
|View full text |Cite
|
Sign up to set email alerts
|

Bladder neck circulation by Doppler ultrasonography in postmenopausal women with urinary stress incontinence

Abstract: The blood flow around the bladder neck in women can be measured by perineal color Doppler ultrasonography. Hormone replacement therapy increases the blood flow around the bladder neck in postmenopausal women with USI. The clinical improvement of USI can be seen with HRT after 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…It has been reported that estrogen deficiency has effects on the female lower urinary tract similar to those in the reproductive tract8, 17, 18. Hypoestrogenism may be responsible for the higher vascular resistance to urethral blood flow in postmenopausal women8, 19.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that estrogen deficiency has effects on the female lower urinary tract similar to those in the reproductive tract8, 17, 18. Hypoestrogenism may be responsible for the higher vascular resistance to urethral blood flow in postmenopausal women8, 19.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that estrogen deficiency has effects on the female lower urinary tract similar to those in the reproductive tract8, 17, 18. Hypoestrogenism may be responsible for the higher vascular resistance to urethral blood flow in postmenopausal women8, 19. Pinggera et al 19 reported that topical estrogen was associated with increased power Doppler signal intensity and reduced RI of the urethral arteries, but Girao et al 17 did not find that systemic estrogen therapy had any effect on vascular resistance of the urethral vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known, that the doppler flow spectrum may be impaired by a number of factors such as ageing, body mass index, menopause, sex hormones profile,(Yang et al 2006; Kobata et al 2008; Tsai et al 2001; Jármy-Di Bella et al 2000; Palmieri et al 2007; Miodrag et al 1988) movement and breathing artifacts as well as by the ultrasonographic access and equipment used (Wieczorek et al 2011). Until now, the most widely used ultrasound technique has been the transperineal/translabial approach.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging of periurethral tissue for analysis of its blood supply has been independently proposed by Tsai and Liang. In the first study, hormone replacement therapy was found to result in a significant decrease of the pulsatility index in the BN area and in a subjective improvement of UI in 17 of 31 women 9. In the second study, decreased periurethral vessels and flow was found in women suffering from SUI when compared to controls, suggesting a possible role of urethral vasculature in the pathophysiology of SUI 10.…”
Section: Methodsmentioning
confidence: 93%